2016
DOI: 10.1159/000446949
|View full text |Cite
|
Sign up to set email alerts
|

Is Maternal Blood Procalcitonin Level a Reliable Predictor for Early Onset Neonatal Sepsis in Preterm Premature Rupture of Membranes?

Abstract: Background: This study is aimed at comparing the early diagnostic accuracy of maternal blood white blood cell (WBC) count, C-reactive protein (CRP) and procalcitonin in predicting early onset neonatal sepsis (EONS) among early preterm premature rupture of membrane (PPROM) pregnancies. Methods: A total of 57 consecutive pregnancies, complicated with PPROM, between 24 and 34 gestational weeks were recruited to the study at Suleymaniye Maternity Education and Research Hospital, Istanbul, Turkey between January 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
22
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 25 publications
3
22
0
2
Order By: Relevance
“…The retrospective aspect of the study was one limitation, in that we were limited to the revision of collected clinical data, unable to collect further studies during subject hospitalization. For example, it was not possible to evaluate the utility of other previously studied biomarkers in NS, such as procalcitonin, 1,22,23 as this paraclinical measurement is not ordered as a routine test in the HUHMP NICU. Similarly, routine laboratory work did not include peripheral blood smears for estimating immature and mature neutrophil counts, which have been previously shown to have diagnostic utility for NS.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The retrospective aspect of the study was one limitation, in that we were limited to the revision of collected clinical data, unable to collect further studies during subject hospitalization. For example, it was not possible to evaluate the utility of other previously studied biomarkers in NS, such as procalcitonin, 1,22,23 as this paraclinical measurement is not ordered as a routine test in the HUHMP NICU. Similarly, routine laboratory work did not include peripheral blood smears for estimating immature and mature neutrophil counts, which have been previously shown to have diagnostic utility for NS.…”
Section: Discussionmentioning
confidence: 99%
“…►Supplementary Table 1 (available in the online version) shows the percentage of missing data for each variable. PCT and membrane rupture time were excluded due to the high percentage of missing data (>30% 1). None of the deliveries were assisted and none of the mothers had records of psychoactive drug use during pregnancy.…”
Section: Sociodemographic Characteristics and Those Related To Their mentioning
confidence: 99%
See 1 more Smart Citation
“…found that maternal blood PCT has higher specificity and positive predictive value in the detection of CA compared with CRP. Another study showed that maternal blood PCT is superior to CRP and WBC in predicting early‐onset neonatal sepsis (EONS) caused by CA . However, some researchers believe that maternal blood PCT cannot precisely predict CA .…”
Section: Introductionmentioning
confidence: 99%
“…High predictive value of PCT for early onset neonatal sepsis was found in another study. High maternal PCT predicted neonatal sepsis with >85% sensitivity, 87% specificity, 85% positive predictive value and 87% negative predictive value . However, reference values for PCT in pregnancy have not been established and PCT levels should always be considered on an individual patient level, taking in account the clinical condition of the patient.…”
mentioning
confidence: 99%